2021
DOI: 10.3390/microorganisms9010168
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Production of β-Caryophyllene and Evaluation of Its Activity against Plant Pathogenic Fungi

Abstract: Terpenoids constitute one of the largest and most diverse groups within the class of secondary metabolites, comprising over 80,000 compounds. They not only exhibit important functions in plant physiology but also have commercial potential in the biotechnological, pharmaceutical, and agricultural sectors due to their promising properties, including various bioactivities against pathogens, inflammations, and cancer. In this work, we therefore aimed to implement the plant sesquiterpenoid pathway leading to β-cary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 125 publications
1
14
0
Order By: Relevance
“…Caryophyllene was found to be cytotoxic and antimicrobial [10]. The effect of caryophyllene in inhibiting the colony growth of several types of fungi tested in this experiment was also reported on several types of fungi including Sclerotinia sclerotiorum, Fusarium oxysporum, Alternaria brassicicola, Phoma lingam, and Rhizoctonia solani [11]. As shown in Figures 1, 2, and 3, the fungistatic effect can be caused by caryophyllene and hexadecanoic acid through inhibition of fungal hyphae cell growth of entomopathogenic agents Me-Sdj-17 and Be-Sdj-13, and Be-Sj-15 at 72 and 96 HAI, Trichoderma (Tc-Ba-05 and Tc-Sdj-18), and As-Sdj-11 and Pn-Sdj-14.…”
Section: Trichoderma Fungi Isolates Of Biofertilizer Agentsupporting
confidence: 69%
“…Caryophyllene was found to be cytotoxic and antimicrobial [10]. The effect of caryophyllene in inhibiting the colony growth of several types of fungi tested in this experiment was also reported on several types of fungi including Sclerotinia sclerotiorum, Fusarium oxysporum, Alternaria brassicicola, Phoma lingam, and Rhizoctonia solani [11]. As shown in Figures 1, 2, and 3, the fungistatic effect can be caused by caryophyllene and hexadecanoic acid through inhibition of fungal hyphae cell growth of entomopathogenic agents Me-Sdj-17 and Be-Sdj-13, and Be-Sj-15 at 72 and 96 HAI, Trichoderma (Tc-Ba-05 and Tc-Sdj-18), and As-Sdj-11 and Pn-Sdj-14.…”
Section: Trichoderma Fungi Isolates Of Biofertilizer Agentsupporting
confidence: 69%
“…The methanolic extract was poorly active since it inhibited only around 50% of mycelial growth of the three fungi (Santos et al, 2024). In sum, this study suggests that antifungal activity exhibited by HE-RB and HE-UB may be explained by their high concentrations of E-caryophyllene, since this sesquiterpene has well-known antifungal activity (Nogueira et al, 2020;Hilgers et al, 2021). Another possibility that must also be mentioned is the synergic effect of all constituents of the extracts which act to result in satisfactory antifungal activity (Rueangrit et al, 2019).…”
Section: Discussionmentioning
confidence: 77%
“…Several reports have shown that both β-caryophyllene oxide and β-caryophyllene possess significant anti-cancer properties, inhibit the growth and proliferation of numerous cancer cell lines [ 24 , 25 , 26 , 27 , 28 ], and are able to enhance the antiproliferative effect of classical anticancer agents, such as 5-fluorouracil, oxaliplatin, paclitaxel, and doxorubicin [ 29 , 30 , 31 , 32 ]. In addition, both of these compounds were found to exhibit anti-inflammatory [ 33 , 34 ], analgesic [ 26 , 35 ], antifungal [ 36 , 37 ], and antibacterial activities [ 28 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%